Assessing the Monetary Value and Environmental Impact of Household Food Waste in Italy - Antonelli, Marta; Giordano, Claudia; Chiriacò, Maria Vincenza; Casari, Silene; Cadel, Elena; Chen, Pin-Jane; Magnani, Andrea; Pizzileo, Gabriele; Falasconi, Luca; Alboni, Fabrizio; Cicatiello, Clara (MDPI, 2024)
Household food waste accounts for a significant share of total food waste. In 2022, around 1.05 billion tons of food waste were generated—60% of which came from households. In the EU, households generate 54% of the total food waste. In Italy, according to a former diary study, avoidable household food waste accounts for 529.9 g per capita per week. Building on this data, this study assesses the monetary value of food waste at the household level in 6 provinces across the country, considering the prices of food items recorded by the Italian Observatory of market prices. Moreover, the environmental impacts of household food waste (greenhouse gas emissions, water consumed, and land used) were investigated based on existing data from well-grounded scientific literature. The results show that the monetary value of food waste ranges from EUR 357.43 to EUR 404.62 per household per year, corresponding to 5–7% of the average household expenditure for food. The environmental impacts per household per year account for 149 kgCO2eq, which contributes to climate change. In addition, household food waste is responsible for 303,498 L of water consumed and 1426 m2 of land used. The results of this study can be integrated into National Energy and Climate Plans (NECPs), to integrate food waste reduction into energy savings and greenhouse gas mitigation strategies.
Keywords: household food waste; monetary value; carbon footprint; environmental impact; Italy